"GET SMALLER"? Emerging geographies of micro‐living. Issue 3 (20th May 2020) - Harris, Ella; Nowicki, Mel
Abstract : Cities across the world are in the grip of an intensifying housing crisis, in which access to affordable, secure, and appropriate housing is increasingly inaccessible for the majority. There is rising pressure on stakeholders to find solutions but, simultaneously, persistent opposition to housing models that contest the neoliberal logics which prioritise housing's financialisation. In this context, many proposed and developed "solutions" have focused on how housing can – in the words of one entry to an architectural competition – "GET SMALLER." Termed "micro‐living, " a trend is emerging for housing models that shrink living spaces, either by providing self‐contained units at below minimum space standards or by offering "co‐living" tenancies in small private rooms with access to shared communal spaces. Presented as innovative and aspirational, micro‐living distinguishes itself from unequivocally problematic small housing, such as Hong Kong's "coffin homes" or the UK's "beds‐in‐sheds." While micro‐living is transforming ways of imagining, producing, and inhabiting cities, it has, as yet, been little explored by geographers. Responding to this gap, this paper traces the emerging geographies of micro‐living in major Western cities and demonstrates the importance of the topic in Geography. As well as detailing micro‐living's typologies, we excavate the lineages of micro‐living and consider the discourses it draws on in self‐presenting as an aspirational form of homemaking. In doing so, we highlight some of the issues that micro‐living responds to, exacerbates, and entrenches, including the stunted opportunities of millennials since the 2008 recession and the precarity of contemporary labour economies. Abstract : This paper traces the emerging geographies of micro‐living in major Western cities and demonstrates the importance of the topic in Geography. As well as detailing micro‐living's typologies, we excavate the lineages of micro‐living and consider the discourses it draws on in self‐presenting as an aspirational form of homemaking. In doing so, we highlight some of the issues that micro‐living responds to, exacerbates, and entrenches, including the stunted opportunities of millennials since the 2008 recession and the precarity of contemporary labour economies.